A revision of Hynobius stejnegeri, a lotic breeding salamander from western Japan, with a description of three new species (Amphibia, Caudata, Hynobiidae) - Tominaga, Atsushi; Matsui, Masafumi; Tanabe, Shingo; Nishikawa, Kanto (Zootaxa, 2019)
A lotic-breeding salamander Hynobius stejnegeri, formerly called H. yatsui, from western Japan is revised based on genetic and morphological evidence, and three species are described: H. guttatus sp. nov. from Chubu-Kinki districts of Honshu Island, H. tsurugiensis sp. nov. from east highland of Shikoku Island, and H. kuishiensis sp. nov. from other parts of Shikoku Island. Thus, H. stejnegeri sensu stricto is restricted to Kyushu Island. Of these four species, H. kuishiensis sp. nov. contains two distinct mitochondrial lineages, but this split is not reflected in differentiation of allozyme (nuclear genome) markers. These species are morphologically similar to each other but can be differentiated by several characteristics, especially in combination of dorsal coloration, the number of vomerine, upper, and lower jaw teeth, and depth of vomerine teeth series. In coloration, H. guttatus sp. nov. is brown or dark brown mostly with tiny white to brownish white marking, while H. tsurugiensis sp. nov. is dark brown with bright yellow continuous markings. Hynobius kuishiensis sp. nov. is reddish purple or dark brown with small to continuous brownish white markings, in contrast to reddish purple or dark brown with small to large brownish white markings in H. stejnegeri.